FOOD PROCESSING, BIOCHEMISTRY AND AGRICULTURE - Diaz, Sara Diana Garduno (DELVE Publishing, 2020)
Food Processing, Biochemistry and Agriculture discusses the basics of the food processing industry such as the importance and history of the food processing sector. The role of agriculture in production of food, basic principles of the food processing industry, production and processing of food crops have been elucidated. The production and processing of dry cereals, legumes, livestock products, soft and natural beverages were explained in this book. The factors that can affect the food processing industry and the emerging issues in the food processing and production are discussed in this book.